THE STUDENTS’ WRITING PROFICIENCY IN DESCRIPTIVE PARAGRAPH WITH PERSONAL PHOTOGRAPH - St Asmayanti; Ardi Hajaruddin (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2017)
The objective of the research was intended to find out the students improvement of writing the descriptive paragraph in term of organization and content; to explain whether or not using personal photograph can increase the students’ writing in the descriptive paragraph. This research used Classroom Action Research that consisted of two cycles. The research population was the second-grade students of SMA Negeri 1Cendanain academic 2014/2015. The sample of this research consisted of 23 students. The instrument used for measuring the students' ability scoring the student was a written test. The findings of the research were (1) the students’ sentence organization  achievement was increased 3,6% from pretest to cycle 1 and was increased 8,8% from cycle 1 to cycle 2. (2) the students’ sentence content achievement was increased 4,3% from pretest to cycle 1 and was increased 8,9% from cycle 1 to cycle 2. From the finding of the research, it indicated that using personal photograph can increase the students’ writing proficiency.